Teaching at The Right Level pada Model PBL Berbasis Digital untuk Meningkatkan Hasil Belajar Matematika dan Kesehatan Mental Siswa SMK - Mauliddha Rachmi; Nugroho Dwi Susanto; Hanna Arini Parhusip; Fika Widya Pratama (Departement of Mathematics Education, 2024)
This research aims to improve mathematics learning outcomes and mental health of class with the digital-based Problem Based Learning model and Teaching at The Right Level approach. This research method is collaborative classroom action research with 3 stages, namely planning, acting and observing, as well as reflecting. The data sources for this research are the results of material knowledge tests and the MHC-SF mental health questionnaire. This research consisted of pre-cycle, cycle I, and cycle II with the percentage of mathematics learning outcomes increasing from 22.2% in the pre-cycle to 83.3% in cycle I and 86.1% in cycle II. Meanwhile, the percentage of student’s mental health in the flourishing category was 19.4% in the pre-cycle, increasing to 50% in cycle I and 69.4% in cycle II.